Konsep Al-'Adah Muhakkamah Dalam Pewarisan Tanah Adat Menurut Adat Perpatih Di Malaysia - Setiyawan Gunardi; Amir Husin Mohd Nor; Azman Ab. Rahman; Mahmoud Mohamed Ali; Nik Rahim Nik Wajis; Mohamad Ikwan Hami; Mualimin Mochammad Sahid; Muneer Ali Abdul Rab; Fithriah Wardi (Universiti Sains Islam Malaysia, 2024)
Malaysian Journal of Syariah and Law Volume 7 No.1 Page (161-177)